Penerapan Kompensasi pada Distro Syaichona Persepektif Maqashid Syariah - Abd Wahid (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2023)
This study aims to determine, analyze and understand the extent of the application of Islamic economics in terms of compensation at the shichona distro from the maqashid sharia perspective. This type of research is descriptive qualitative research based on the results of interviews and documentation using analysis techniques from Miles and Hubberman. The results showed that Distro Syaichona in compensating employees there are two types of compensation namely direct compensation and indirect compensation. Direct compensation provided by Distro Syaichona is in the form of salaries, incentives and allowances. While indirect compensation is in the form of social assistance and employee welfare. In this case, social assistance is in the form of death assistance, calamities and money lending. The application of compensation from the maqashid sharia perspective carried out by Distro Syaichona has not fully implemented hifdz al-mal in accordance with Islamic economics, the contributing factor is that Distro Syaichona has not implemented the principle of not delaying employee rights properly, because there is still a delay in providing compensation even though it is not too frequent. But on the other hand, Syaichona Distro applies the principle of hifdz al-din which is in accordance with Islamic economics, namely the principle of fairness and worthiness.